Mutual fund Performance in Nepalese Mutual fund units: An analysis of Monthly Returns - Bajracharya, Rajan Bilas (Journal of Advanced Academic Research, 2017)
Mutual funds dwell in a small market in Nepal. Around seven mutual funds listed in the Nepal stock exchange trade (NEPSE). This paper focused on evaluating the performance of five mutual funds of NEPSE on the basis of monthly returns compared to benchmark return. Risk adjusted performance measures suggested by Jenson, Treynor, Sharpe and statistical models are employed. It is found that, most of the mutual funds have performed better according to Jenson and Treynor measures but not up to the benchmark on the basis of Sharpe ratio. However, few mutual funds are well diversified and have reduced its unique risk.  Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 92-100